Analysis of nonlinear responses of asphalt pavements under overloading and tropical climate temperature conditions - Kumar A.; Gupta A.; Anupam K.; Premarathna W.A.A.S. (My University, 2025)
The design of asphalt pavement in many developing nations still relies on an empirical approach, often leading to either premature failure of the pavement or overdesign. The transition from an empirical approach to semi-mechanistic or mechanistic was felt by past researchers, and many advanced tools based on these approaches have been developed. Computational tools, like finite element (FE) analysis, are capable of handling complex material properties of pavement materials under nonuniform loading conditions. Asphalt mixes are widely known to exhibit viscoelastic behaviour based on temperature and loading conditions, while the response of unbound materials under cyclic loading is stress dependent. Due to the complexity of the entire process, numerous pavement design tools treat them as purely elastic materials. This study aims to develop a finite element based, simple, and practical framework to assess the structural response of asphalt pavement under overloading and varying temperature conditions in a tropical climate. The framework offers a straightforward method for the determination of time dependent viscoelastic parameters of the asphalt mixture using creep compliance test. The nonlinear stress-dependent behaviour of unbound granular materials (UGMs) in different layers has also been presented based on repeated load triaxial compression testing. It was concluded that overloading and increasing mix temperature severely affect pavement performance. A 25 % overloading resulted in a reduction of subgrade rutting life by 62.33 %, whereas an increase in mix temperature by 10° C at intermediate temperature reduced asphalt fatigue life by 29.34 % and subgrade rutting life by 42.03 %. © 2025 The Authors